Proceedings 2016 Workshop on Usable Security 2016
DOI: 10.14722/usec.2016.23022
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Saudis' Privacy Concerns When Using WhatsApp

Abstract: Managing privacy in mobile instant messaging is a challenge for designers and users alike. If too many options are provided, the privacy controls can become complex to understand and unwieldy to manipulate. Conversely, providing too few controls leaves users without the ability to adequately express their privacy preferences. Further complicating this, a new class of social networks has emerged where one person can add another without mutual consent (i.e. Tumbler, Twitter, and WhatsApp). We present a survey of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 26 publications
3
21
0
Order By: Relevance
“…According to Ajlan, his close community presence and activity played a significant role in helping him to accept the utilization of WhatsApp in his English language learning. This finding is parallel with the research by Rashidi, Vaniea, & Camp (2016), who also found a positive correlation between the close community of the learner and the learner's technological utilization. I am currently working on another study where I applied Twitter to be used as a tool for English learning with the same participants in the classroom.…”
Section: Community Relationshipsupporting
confidence: 86%
“…According to Ajlan, his close community presence and activity played a significant role in helping him to accept the utilization of WhatsApp in his English language learning. This finding is parallel with the research by Rashidi, Vaniea, & Camp (2016), who also found a positive correlation between the close community of the learner and the learner's technological utilization. I am currently working on another study where I applied Twitter to be used as a tool for English learning with the same participants in the classroom.…”
Section: Community Relationshipsupporting
confidence: 86%
“…One of the few studies in this area, by Rashidi et al, examined the privacy practices of WhatsApp users in the Kingdom of Saudi Arabia [27]. This study found that many users had changed their privacy settings and had blocked unwanted contact, but also wanted more control over their privacy.…”
Section: Recent Disclosures Of Government Surveillance In the Unitedmentioning
confidence: 99%
“…Two papers have examined questions relating to use of security and privacy features in secure messaging applications in particular countries. Rashidi et al conducted a study of the privacy practices of 626 WhatsApp users in the Kingdom of Saudi Arabia [27]. They found that majority (59%) had changed at least one privacy setting, with about 45% changing who could see their last seen status, while about 25% changed who could see their profile photo or status.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding WhatsApp, there are specific motivators linked to cost, sense of community, and immediacy [16], as well as to unlocking new opportunities for intimate communication [17]; addictive behaviors have even been detected toward the application [18]. A number of studies about the use of this innovative technology have been conducted [19], which have detected a series of factors that positively or negatively influence the use of WhatsApp, such as the importance of family groups [20], the use of status within the application [21], interactions with the education field [22,23], and concerns about privacy [24], among others. This study intends to analyze WhatsApp consumer behavior from the perspective of the variables that influence the intention to use this technology and to determine what these variables are and how they articulate to affect the intention to use WhatsApp, using the variables proposed in the UTAUT2 model [4].…”
Section: Introductionmentioning
confidence: 99%